Life at the margins of the state : comparative landscapes from the old and new worlds - Boswell, Alicia M.; Knabb, Kyle A. (University Press of Colorado, 2022)
"This book examines the sociopolitical and cultural strategies of resistance developed by marginal communities. Case studies from historic California, Medieval Iceland, ancient Mesoamerica, ancient Nubia, Colonial El Salvador, the prehistoric Levant, pre-Columbian Amazon, Africa's historic central Sahel, and ancient Peru, offer perspectives on how societies adapted to these liminal spaces."--